Volume Infusion Markedly Increases Femoral dP/dtmax in Fluid-Responsive Patients Only*. Issue 10 (October 2020) - Vaquer, Sergi; Chemla, Denis; Teboul, Jean-Louis; Ahmad, Umar; Cipriani, Flora; Oliva, Joan Carles; Ochagavia, Ana; Artigas, Antonio; Baigorri, Francisco; Monnet, Xavier
Abstract : Objectives: To evaluate the preload dependence of femoral maximal change in pressure over time (dP/dtmax ) during volume expansion in preload dependent and independent critically ill patients. Design: Retrospective database analysis. Setting: Two adult polyvalent ICUs. Patients: Twenty-five critically ill patients with acute circulatory failure. Interventions: Thirty-five fluid infusions of 500 mL normal saline. Measurements and Main Results: Changes in femoral dP/dtmax, systolic, diastolic, and pulse femoral arterial pressure were obtained from the pressure waveform analysis using the PiCCO2 system (Pulsion Medical Systems, Feldkirchen, Germany). Stroke volume index was obtained by transpulmonary thermodilution. Statistical analysis was performed comparing results before and after volume expansion and according to the presence or absence of preload dependence (increases in stroke volume index ≥ 15%). Femoral dP/dtmax increased by 46% after fluid infusion in preload-dependent cases (mean change = 510.6 mm Hg·s –1 ; p = 0.005) and remained stable in preload-independent ones (mean change = 49.2 mm Hg·s –1 ; p = 0.114). Fluid-induced changes in femoral dP/dtmax correlated with fluid-induced changes in stroke volume index in preload-dependent cases ( r = 0.618; p = 0.032), but not in preload-independent ones. Femoral dP/dtmax strongly correlated with pulse and systolic arterial pressures and with total arterial stiffness, regardless of the preload dependence status ( r > 0.9 and p < 0.001 in all cases). Conclusions: Femoral dP/dtmax increased with volume expansion in case of preload dependence but not in case of preload independence and was strongly related to pulse pressure and total arterial stiffness regardless of preload dependence status. Therefore, femoral dP/dtmax is not a load-independent marker of left ventricular contractility and should be not used to track contractility in critically ill patients. Abstract : Supplemental Digital Content is available in the text.